Female sterilization at BAVS clinic and camp, Bangladesh - Sultana Begum (Technical report (Bangladesh Fertility Research Programme) ;, 1977)
Report of a 1975-1976 female sterilization program at the clinic and rural camps of the Bangladesh Association for Voluntary Sterilization.